2001
DOI: 10.4049/jimmunol.166.3.1583
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Converting Enzyme Cleaves the Macrophage Colony-Stimulating Factor Receptor in Macrophages Undergoing Activation

Abstract: We previously reported that macrophage activators such as LPS, IL-2, and IL-4 down-modulate the M-CSFR via a mechanism involving protein kinase C and phospholipase C. In this study, we showed that M-CSFR is shed from macrophage surface and identified the protease responsible for M-CSFR cleavage and down-modulation. The shedding of M-CSFR elicited by phorbol esters (tetradecanoylphorbol myristate acetate (TPA)) or LPS in murine BAC.1-2F5 macrophages was prevented by cation chelators, as well as hydroxamate-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 41 publications
7
89
0
Order By: Relevance
“…This is consistent with an observation showing that there is no increase in CSF-1 receptor phosphorylation upon activation of PKC (22). It has been found recently that release of the extracellular domain of the CSF-1 receptor is mediated by TACE (59). TACE is a cell surface-associated metalloprotease that is composed of an extracellular catalytic domain, a transmembrane domain, and a small cytoplasmic domain (34).…”
supporting
confidence: 75%
“…This is consistent with an observation showing that there is no increase in CSF-1 receptor phosphorylation upon activation of PKC (22). It has been found recently that release of the extracellular domain of the CSF-1 receptor is mediated by TACE (59). TACE is a cell surface-associated metalloprotease that is composed of an extracellular catalytic domain, a transmembrane domain, and a small cytoplasmic domain (34).…”
supporting
confidence: 75%
“…Shedding of the receptor by PKC activators generates a soluble form that is still competent for ligand binding, and down-modulates CSF-1 signaling and inactivates macrophages. CSF-1 receptor shedding is blocked by metalloprotease inhibitors as well as by an antibody to the catalytic site of ADAM17 (Rovida et al 2001). The reduction of cell surface CSF-1 receptor by TPA treatment is also effectively abolished in ADAM17 deficient monocytes.…”
Section: Growth Factor Receptorsmentioning
confidence: 99%
“…Total STAT1 levels served as an internal control within the experiment. We and others showed that LPS and CpG DNA caused a loss of cell surface CSF-1R due to cleavage of the extracellular domain, whereas IFN-␥ only modestly down-regulated cell surface CSF-1R expression (34,36,42,43). Consistent with these previous findings, CSF-1R levels in extranuclear extracts were markedly reduced in response to LPS and CpG DNA, but were only modestly affected by IFN-␥ (Fig.…”
Section: Cpg Dna Activates Serine But Not Tyrosine Phosphorylation mentioning
confidence: 99%